Uncovering Barriers in Forecasting Uncertain Product Demand in the Supply Chain - Elias Abou Maroun; Didar Zowghi; Renu Agarwal; Babak Abedin (International Journal of Supply Chain Management, 2022)
This paper aims to provide insights into the barriers of forecasting uncertain product demand in supply chain by focusing on the relative importance of the barriers for businesses, particularly the forecast practitioners and prospective forecast implementers. A exploratory, qualitative approach was adopted within an Australian electrical manufacture. Data was gathered through semi-structured interviews with 20 participants from different departments, including forecasting practitioners, supplier and customer of the Australian electronics manufacturer. Thematic analysis was conducted to confirm some of the existing barriers reported in the literature and identify emerging barriers from practice in industry. The study reveals that there are more barriers to choosing the right forecasting system or method and the main reason for poor forecast performance is intertwined between cultural, communication, product, market, environmental and technological themes. These themes lend empirical insights into the barriers still faced in many organisation today. The identification of end to end barriers in forecasting uncertain product demand of the electrical manufacturing industry have not previously been studied in great depth. This paper sheds insight, provides new knowledge and contributes to academic thinking.